1988
DOI: 10.1021/bi00417a037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cholesterol on sodium-potassium ATPase ATP hydrolyzing activity in bovine kidney

Abstract: The (Na+,K+)-ATPase ATP hydrolyzing activity from rabbit kidney medulla basolateral membrane vesicles was studied as a function of the cholesterol content of the basolateral membranes. The cholesterol content of the membranes was modified by incubation with phospholipid vesicles. When the cholesterol content was increased above that found in the native membrane, the (Na+,K+)-ATPase ATP hydrolyzing activity was inhibited. When the cholesterol content was decreased from that found in the native membranes, the (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
88
0
2

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(101 citation statements)
references
References 19 publications
11
88
0
2
Order By: Relevance
“…Prior treatment of the apical membrane with nystatin removed any rate limitation associated with Na ϩ entry into the cell, thus demonstrating the inhibition was most likely due to cholesterol-mediated effects on the Na ϩ pump. Cholesterol has also been shown to be critical for Na-K-ATPase activity in other cell types including renal cells (34). To verify that the effect was indeed localized to the ATPase on the basal membrane we performed a similar experiment in which we pretreated cells apically or basally with m-CD then permeabilized the apical membrane with nystatin and subsequently quantitated the amount of ouabain inhibitable current remaining.…”
Section: Resultsmentioning
confidence: 99%
“…Prior treatment of the apical membrane with nystatin removed any rate limitation associated with Na ϩ entry into the cell, thus demonstrating the inhibition was most likely due to cholesterol-mediated effects on the Na ϩ pump. Cholesterol has also been shown to be critical for Na-K-ATPase activity in other cell types including renal cells (34). To verify that the effect was indeed localized to the ATPase on the basal membrane we performed a similar experiment in which we pretreated cells apically or basally with m-CD then permeabilized the apical membrane with nystatin and subsequently quantitated the amount of ouabain inhibitable current remaining.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have shown that cholesterol affects the behavior of membrane inserted helices and the function of many membrane-associated proteins directly or by means of its effect on the physical properties of the phospholipid bilayer, i.e., bilayer hydrophobic thickness and material moduli (35)(36)(37)(38)(39)(40)(41)(42). For example, cholesterol can stabilize ␣-helices in membrane proteins (43,44); it also affects the function of many membrane proteins (36,39,(45)(46)(47)(48) and can alter ion channel gating (49-51).…”
Section: Quantitative Measurements Of Peptide Association In Phospholmentioning
confidence: 99%
“…These effects of cholesterol enrichment on the activity of membrane proteins have been observed in erythrocytes, 52 vascular cells, 53 and renal cells. 54 In vascular SMCs obtained from atherosclerotic plaque, calcium transport mechanisms and basal intracellular calcium levels are disrupted as a result of increased membrane cholesterol content. 55 These changes have important consequences for atherosclerosis, as calcium participates directly in signal transduction pathways that promote SMC proliferation and migration, among other changes.…”
Section: Alterations In Vascular Cell Membrane Function Due To Cholesmentioning
confidence: 99%